Abandoning the Black Hero : Sympathy and Privacy in the Postwar African American White-Life Novel. - Charles, John C. (Rutgers University Press, 2012)
Abandoning the Black Hero examines the motivations that led certain African American authors in mid-twentieth century to shift from writing protest novels about racial injustice to novels focusing primarily, if not exclusively on whites, or white-life novels. These fascinating works have been understudied despite having been written by such defining figures as Richard Wright, Zora Neale Hurston, James Baldwin, Ann Petry, and Chester Himes, as well as lesser known but formerly best-selling auth.